Should corporate debt include a rating trigger? - Bhanot, Karan; Mello, Antonio S. (Journal of Financial Economics, 2006)
Recent corporate debt offerings have included a covenant specifying a pre-determined payment to debtholders when the debt is downgraded. We examine the incentive for equityholders to increase firm risk (and the associated costs) when debt includes a “rating trigger.” Equityholders of firms with a low-risk profile and operating flexibility choose debt with a trigger, while equityholders of firms with a high-risk profile and less flexibility choose regular debt. A trigger that requires an equity infusion better mitigates conflicts between equityholders and debtholders than a trigger paid by liquidating assets. A trigger that increases the coupon rate is not optimal.